PELATIHAN BUDIDAYA TANAMAN HIAS SECARA VERTIKULTUR GUNA PEMANFAATAN BOTOL BEKAS DI DAERAH PERKOTAAN - Annisa Zukhruf O.S; Fiqri Isighfarul H; Mareta Dwi S; Petrus Siregar; Sabrina Adha Y.; Sasiska Rani; Susi Hardjati (STIE Trisna Negara, 2022)
Garbage is useless material left over from the activities of living things. Waste is divided into two, namely organic waste and inorganic waste. Inorganic waste such as paper, iron, glass, cables, light bulbs, and plastic are waste that takes a long time to decompose. One of the solutions that can be done to reduce the amount of inorganic waste in urban areas is recycling. This plastic bottle can be used as a place to grow crops. The advantage of using plastic bottles for farming activities is that it saves space and is environmentally friendly. This can support reforestation programs in urban areas where there is little space to be used as green open spaces. The training is carried out in two stages, namely: Preparation: Meeting with partners; Pre-survey location. At this stage, it is explained how the process of implementing vertical cultivation of ornamental plants by using used bottles is explained. Implementation: Making plant pots from used plants; decorate pots that have been made with paint so that they look more attractive; transfer the available seeds to the media in pots; install pots that have been made in the locations that have been surveyed. The result of the training in verticultural ornamental plant cultivation is that it can attract people to create or use verticulture techniques to grow crops at home which can be an alternative to ornamental plant culture in limited or narrow land. Keywords: plastic bottles, ornamental plants, verticulture, urban